Religious Life of Contemporary Muslim Women at Work - nabil amir, ahmad (International Conference on Multidisciplinary Issues (INCOMI), 2024)
This work surveys the basic socio-ethical and cultural life of Muslims women in Malaysia since colonial era. It brought to light their encouraging works that help to realize many social, political, religious and economic potential in facing global problems and its highly sophisticated challenge and predicament. Their social presence had largely facilitated effort toward social cohesion and enriching fundamental discourse on modernity, religious and democratic values. The study takes particular interest in the horizon of their religious life and its significance in enriching the cultural fabric of civil society and its societal make-up and spiritual foundation. principles in the spirit of dialogue and religious Convivencia. This work also looks into how this essentially affect their work in dealing with difference ideology in the context of social interaction and different worldview they have with each other